Pengaruh Penurunan Nilai Kadar Abu Terhadap Nilai Kadar Zat Menguap Pada Briket Kulit Jengkol: The Effect of Decreasing Ash Content Value on Vaporized Substance Content Value of Jengkol Skin Briquettes - Fazira, Natasya Aulia; Masthura; Ety Jumiati (JFT : Jurnal Fisika dan Terapannya, 2023)
The purpose of this research is to make briquettes of jengkol skin waste using sago starch adhesive so that it is known to reduce the value of ash content to the value of volatile matter content. The ratio of jengkol skin waste charcoal to sago starch glue used in this study ranged from sample A 65:35, B 70:30, C 75:25, D 80:20. The concentration of ash and volatile chemicals were among the variables analyzed. Sample D, containing 80% jengkol skin charcoal and 20% sago adhesive, performed best in terms of ash content (5.99%) and volatile matter content (4.03%) when tested as a charcoal briquette composition. SNI 01-6235-2000 which is the standard for wood charcoal briquettes has been fulfilled by the briquettes. Keywords: Jengkol Skin, Charcoal Briquettes, and Sago Flour.